2012
DOI: 10.3168/jds.2012-5404
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in lactating Holstein cows supplemented with Cu, Mn, and Zn as sulfates or methionine hydroxy analogue chelates

Abstract: The aim of this study was to compare effects of inorganic sulfate versus chelated forms of supplemental Cu, Mn, and Zn on milk production, plasma and milk mineral concentrations, neutrophil activity, and antibody titer response to a model vaccination. Holstein cows (n = 25) were assigned in 2 cohorts based on calving date to a 12-wk randomized complete block design study. The first cohort consisted of 17 cows that had greater days in milk (DIM; mean of 77 DIM at the start of the trial) than the second cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 45 publications
8
43
1
2
Order By: Relevance
“…Engle et al (1997) reported a more pronounced cell response in marginally Zn deficient calves supplemented with Zn-Met and Zn-Lys than in calves supplemented with ZnSO 4 . Nemec et al (2014) reported a greater improvement of the immune status in lactating cows receiving organic Zn compared to those supplemented with inorganic Zn, Cu, and Mn sources. The neutrophil phagocytosis was positively affected in the group supplemented with chelated minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Engle et al (1997) reported a more pronounced cell response in marginally Zn deficient calves supplemented with Zn-Met and Zn-Lys than in calves supplemented with ZnSO 4 . Nemec et al (2014) reported a greater improvement of the immune status in lactating cows receiving organic Zn compared to those supplemented with inorganic Zn, Cu, and Mn sources. The neutrophil phagocytosis was positively affected in the group supplemented with chelated minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, total mineral intake for these groups represents an interaction between exogenously supplemented mineral and DMI. Other research on Cu, Mn and Zn supplementation has ignored mineral content supplied by the feed in analyses or treatment results (DeFrain, Socha, Tomlinson, & Kluth, ; Formigoni et al., ; Nemec et al., ; Nocek, Socha, & Tomlinson, ; Rabiee, Lean, Stevenson, & Socha, ). Therefore, this study is unique in that it attempts to quantify both dietary and exogenously supplied Cu, Zn and Mn effects on milk production, mitochondrial respiration and efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of retention in this study did not include urine excretion. However, milk and urinary excretion of Mn and Zn has been shown to be negligible and not responsive to level of supplementation (Nemec et al., ; Weiss & Socha, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, when the supplementation was at a lower level than recommended, the source had no effect. Nemec et al (2012) evaluated the substitution of inorganic sources of zinc, manganese and copper for organic sources in the feeding of early-lactating dairy cows averaging 40 kg day −1 and found no effect of the source on milk yield, despite the reduction in dry matter intake. Hackbart et al (2010) observed no effect of mineral source in diets for early-lactation dairy cows on feed intake and milk yield of high-producing dairy cows.…”
Section: Resultsmentioning
confidence: 99%
“…Zootec., 44(3):103-108, 2015 Cope et al (2009) reported a 1.4 kg.day −1 increase in milk yield of cows when they received organic zinc sources as compared with inorganic sources, at the level recommended by NRC (2001). On the other hand, studies have found that milk yield does not increase with the use of sources of organic trace minerals (Defrain et al, 2009;Hackbart et al, 2010;Nemec et al, 2012).…”
Section: Introductionmentioning
confidence: 99%